72.6k views
24 votes
Help me, the picture down below

Help me, the picture down below-example-1
User Arshiya
by
5.7k points

2 Answers

3 votes

Answer(s):

y = 2(x - 1)2 + 3

y = 2(x2 - 2x + 1) + 3

y = 2x2 - 4x + 2 + 3

y = 2x2 - 4x + 5

User Jemminger
by
5.6k points
5 votes

Answer:

  • y = -3/4(x + 2)² + 6

Explanation:

Vertex form of quadratic function:

  • y = a(x - h)² + k

Given a graph with:

  • Vertex = (-2, 6)
  • Points: (-6, -6), (2, -6)

We can see that:

  • h = -2 and k = 6, a is negative (parabola opens down)

The equation becomes:

  • y = a(x + 2)² + 6

Substitute coordinates (-6, -6) into the equation to find the value of a:

  • -6 = a(-6 + 2)² + 6
  • -6 = 16a + 6
  • 16a = -12
  • a = -12/16
  • a = -3/4

The function becomes:

  • y = -3/4(x + 2)² + 6
User Jerome Diaz
by
5.9k points